Moderating Effects of Market Based Value on the Relationship Between Financial Performance and Stock Returns: Evidence from the Indonesian Banking Industry - Ciseta Yoda, Tilawatil; Husni, Tafdil; Luthan, Elvira; Rahim, Rida (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2025)
The information that investors receive plays a crucial role in shaping their expectations regarding a firm's future prospects. It serves as a signal of the firm's performance, further amplified by its total market capitalization. This study delves into the relationship between financial performance and stock returns, with market capitalization acting as a moderating variable. Drawing on panel data from banking companies listed on the Indonesia Stock Exchange (IDX) between 2013 and 2022, the research encompasses 363 firm-year observations. Using an Ordinary Least Squares (OLS) estimation model, the findings reveal that market capitalization exerts a positive and significant influence on the relationship between financial performance and stock returns. This suggests that firms with higher market capitalization tend to see a stronger alignment between their financial performance and investor returns, underscoring the value of size and market perception in driving stock price movements.